STUDI TENTANG BATIK KAGANGA KABUPATEN REJANG LEBONG PROVINSI BENGKULU - FAISAL RAFANDI, Drs. Ajusril S., Drs. Erwin A, M.Sn. (Universitas Negeri Padang, 2016)
This article aims to describe the history and development of batik Kaganga, shape motifs and techniques of batik Kaganga.The research method used by the writer through a qualitative descriptive approach. Subjects were informants who know about the object of researchers, among others, employees of the BMA (Balai Musyawarah Adat) and the Women's Batik workshop Bengkulu. Sources of data taken form written records that come from informants who were interviewed, documentation and literature study.The results showed that the history of batik Kaganga began in 1985. The form and source Kaganga batik has its own characteristics, each motif there Rejang alphabet letters combined with some form of nature in Bengkulu like: Rafflesia Bunga Rafflesia motif, Diwo, Bakul Sirih, Kepahiang dan Ikan Mas. batik motifs form a stand-alone Kaganga not sequential, with a stylized way, Extremely Stylized Stylized and the motive, and added Isen Isen on the motif. Kaganga batik making techniques originally used the technique of batik. Along with the times batik cap Kaganga made using techniques that manufacture cheaper and faster but unfortunately the use of these techniques actually make batik Kaganga lost its luster and dropped dramatically.Keywords: History, Development, Form and Technique